PENGARUH COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI KELAS V SEKOLAH DASAR - Wiranata, Ardian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to analyze how much influence the use CIRC (cooperative integrated reading and composition) toward essay writing narrative skill of fifth grade students Elementary School 03 Kubu Raya. This research uses experimental methods Quasy type experiment. The population in this study were all fifth grade students of Elementary School 03 Kubu Raya that consists of two classes, namely VB and VC. Samples were students of class VB (experimental class) accounted for 29 students and VC (grade control) accounted for 27 students. Based on the analysis of data obtained by the average post-test control class average of 75,72 and post-test experimental classroom 83.17. The results of hypothesis testing using t-test (polled variant) for the obtained t = 2,95 df = 54 and ? = 5% was obtained t_tabel of 1.67 which means t_hitung> t_tabel (2,95>1.67), the Ha received. Thus, it can be concluded that there are influence the use CIRC (cooperative integrated reading and composition) toward essay writing narrative skill of fifth grade students Elementary School 03 Kubu Raya.   Keywords : CIRC, Essay Writing Narrative Skill.